MEMBANGUN VIRTUAL TRAVELING KABUPATEN KUTAI KARTANEGARA (KUKAR) SEBAGAI MEDIA WISATA VIRTUAL DI MASA PANDEMI - Siti Lailiyah; Jundro Daud Hasiholan; Muhammad Jahriansyah (Jurnal Ilmiah Matrik, 2021)
large-scale social restriction make tourists no longer able to visit tourist objects freely like they used to. Research to develop Virtual Traveling of Kutai Kartanegara is one of the media that will be used to support tourism in Kutai district during the Covid-19 pandemic, in a fun way so that it will attract millennials to get to know tourism in Kutai Kartanegara (KUKAR) so it is hoped that tourism objects that will become candidates for the new capital city of Indonesia which is better known in the archipelago. Virtual Traveling is an alternative for traveling without having to go far to the city. Virtual tourism can be an interesting medium to introduce various tourist objects in KUKAR through interactive applications. The purpose of establishing Kutai Kartanegara Virtual Traveling is that KUKAR tourism will be easily introduced to the public with interactive and interesting media. In this research, the method used to build a tourism application is multimedia life-cycle development, starts from concept, design, materials collecting, assembly, testing, and distribution. The result, this virtual tourism application can be used as promotional media for the KUKAR Tourism Department